2005
DOI: 10.1073/pnas.0502256102
|View full text |Cite
|
Sign up to set email alerts
|

A genetically defined mouse ovarian carcinoma model for the molecular characterization of pathway-targeted therapy and tumor resistance

Abstract: Cell lines and tumors with defined genetic alterations provide ideal systems in which to test the molecular mechanisms of tumor sensitivity to pathway-targeted therapy. We have generated mouse ovarian epithelial tumor cell lines that contain various combinations of genetic alterations in the p53, c-myc, K-ras and Akt genes. Using both in vitro and in vivo approaches, we investigated the effect of rapamycin on cell proliferation, tumor growth, and the accumulation of peritoneal ascites. We demonstrated that rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…The observation that HOXB13 is expressed in a high percentage of human ovarian cancer cell lines and tumors, and that the expression of HOXB13 in human breast cancer is associated with a more aggressive clinical course compared with breast tumors that do not express HOXB13, raises the possibility that HOXB13 may play an important role in tumor progression. The possibility that HOXB13 promotes ovarian tumor growth was tested by ectopic expression of this gene by replication-competent avian leukosis virus long terminal repeat with splice acceptor (RCAS) retroviral delivery in T1 ovarian cancer cells, a cell line generated from mouse ovarian surface epithelial cells that contains genetic alterations in p53, c-myc, and K-ras (15)(16)(17) and has undetectable expression of endogenous HOXB13 by RT-PCR analysis ( Fig. 2A) and Western blotting (Fig.…”
Section: Knockdown Of Endogenous Hoxb13 In Human Ovarian Cancer Cellmentioning
confidence: 99%
“…The observation that HOXB13 is expressed in a high percentage of human ovarian cancer cell lines and tumors, and that the expression of HOXB13 in human breast cancer is associated with a more aggressive clinical course compared with breast tumors that do not express HOXB13, raises the possibility that HOXB13 may play an important role in tumor progression. The possibility that HOXB13 promotes ovarian tumor growth was tested by ectopic expression of this gene by replication-competent avian leukosis virus long terminal repeat with splice acceptor (RCAS) retroviral delivery in T1 ovarian cancer cells, a cell line generated from mouse ovarian surface epithelial cells that contains genetic alterations in p53, c-myc, and K-ras (15)(16)(17) and has undetectable expression of endogenous HOXB13 by RT-PCR analysis ( Fig. 2A) and Western blotting (Fig.…”
Section: Knockdown Of Endogenous Hoxb13 In Human Ovarian Cancer Cellmentioning
confidence: 99%
“…It seems to be clear that activation of AKT via PI3K occurs through phosphorylation by phosphoinositide-dependent kinase-1 and/or phosphoinositide-dependent kinase-2 at serine and threonine residues (Ser 472/473 , Thr 308 ). Several authors reported that especially phosphorylation of AKT at Ser 473 is associated with resistance to chemotherapy/ radiotherapy (36)(37)(38)(39)(40), and it has been proposed that activated AKT promotes survival of cells exposed to ionizing radiation through inhibition of apoptosis (41,42) or enhancement of DNA double-strand break repair (31).…”
Section: Introductionmentioning
confidence: 99%
“…All of the genetically engineered mouse models described above have the potential for being valuable models of metastatic ovarian cancer. The avian retroviral gene delivery technique described by Orsulic et al is particularly useful for the analysis of different combinations of multiple genetic alterations and their collaboration in tumor initiation and progression [2] aswell asfor testing pathway-targeting therapies [19]. An important advantage of the MISIIR-TAg model is the short latency of metastatic disease because of germline expression of the transgene.…”
Section: Model Comparisonmentioning
confidence: 99%